Anthropological foundations of Edith Stein’s philosophy of education - Kulyk, Andrii (Filosofiya osvity. Philosophy of Education, 2025)
The article examines key aspects of the educational philosophy of the eminent German philosopher Edith Stein through the lens of pedagogical and philosophical anthropology. It analyzes how her profound understanding of human nature, spiritual orientation, and pursuit of truth, goodness, and beauty shape her vision of the purpose, content, and methods of upbringing and learning. Particular attention is given to the thinker’s phenomenological approach to education, her philosophy of personal development within the educational sphere, her ideas on fostering a holistic personality, and the role of the educator in unlocking a student’s potential. For Stein, education isn’t merely preparation for life; it’s a mode of being-in-learning, in which the profound meaning of human existence unfolds. The article analyzes Edith Stein’s work “The Structure of the Human Person”, where the philosopher explores the interrelation between anthropology and pedagogy. When examining her views, one cannot overlook the influence and critique of Martin Heidegger’s ideas, particularly his understanding of Dasein and human nature. She criticizes Martin Heidegger, seeing in his ideas a potential for despair and nihilism, which makes the meaningful education of young people exceedingly difficult. Thus, in her reflections on education and the essence of humanity, Edith Stein, engaging in polemics with Martin Heidegger, emphasizes that education isn’t just about adapting to the existing world or preparing for a profession. Learning aims to help students find their rightful place in the world and recognize their unique worth. This outlined pedagogical axiology emerges as a comprehensive concept, placing values and the spiritual development of the individual at the heart of the educational process. Edith Stein proposes unique methodological approaches rooted in phenomenology and a profound understanding of human nature. The German thinker emphasized that an educator must possess the capacity for empathy – the ability to grasp the feelings, challenges, and aspirations of another.